Research and Implementation of an AI-Based Human Posture Recognition System - Li, Wenjie; Wang, Lei; Ma, Yun; Wang, Zizheng; Hu, Zhanyi; Jian, Youbin (Journal of Contemporary Medical Practice, 2025)
Knee osteoarthritis is a common senile degenerative disease in orthopedics and traumatology. The main characteristics of knee osteoarthritis are joint swelling pain and limited movement, which seriously affects the physical and mental health of patients. Needle therapy has the advantages of quick onset, low cost and better long-term curative effect. This article comprehensively analyzed the research status of the treatment of knee osteoarthritis with fire needle by searching the articles of CNKI, VIP, PubMed and other databases.